Efektivitas pengelolaan penganggaran keuangan daerah terhadap kesejahteran masyarakat di Kota Lhokseumawe - Rahmayati, Cut Aneza; Mahira, Tanasa; Raihan, Nur; Aliffadhila, Muhammad; Zulkarnain, Teuku (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the Village Fund Allocation (ADD) on community welfare in Simpang Empat Village, Lhokseumawe City, Aceh. Village funds are part of the equalization funds used to support development, community empowerment, and improve village welfare. This study also aims to evaluate the effectiveness of village fund management in improving the quality of life of the community through transparent and accountable financial management. The research methods used are qualitative research methods, interviews, and field observations. The results show that the allocation of village funds has had a positive impact on infrastructure development, local economic development, and improved access to education and health. However, there are several obstacles in its implementation, such as limited human resources (HR) and inadequate infrastructure. In addition, the management of natural resources in the village is still not optimal. Therefore, it is necessary to increase the transparency of village fund management and more effective natural resource management to achieve more equitable community welfare.